Pancasila dan demokrasi di indonesia: meneguhkan pancasila sebagai penopang demokrasi di era globalisasi - dwiyanti, siska (Maliki Interdisciplinary Journal, 2025)
Pancasila, as Indonesia’s national ideology, plays a crucial role in shaping a civilized and identity-based democratic system. However, globalization and the rapid growth of digital technology have brought complex challenges to its implementation, including moral degradation, rising social intolerance, and the weakening of national value internalization among citizens and younger generations. This study employs a qualitative descriptive approach with a literature review method to examine Pancasila’s role in strengthening democracy within the global era. The findings indicate that Pancasila must be revitalized to move beyond its symbolic function and serve as a practical foundation for political, social, and economic life. Revitalization can be achieved through promoting social justice in the digital economy, developing inclusive leadership among the youth, and integrating character education and digital literacy into the national education framework. Strengthening these values will reaffirm Pancasila as the moral foundation of Indonesian democracy, ensuring that it remains just, inclusive, and responsive to the challenges of globalization while preserving the nation’s ethical and cultural identity.